The Lpp-OmpA-BtaE fusion protein causes a protective immune response against Brucella melitensis in mice - Maryam Borhan Nobari; Mohamad Reza Razavi; Farzaneh Hosseini; Nour Amirmozafari; Abbas Akhavan Sepahi (Scientific Reports)
Abstract Brucellosis, primarily caused by B. melitensis, is a widespread zoonotic disease with significant economic and public health burdens on a global scale. Given the limitations of existing vaccines and the potential advantages associated with subunit vaccines, prioritizing the development of efficacious Brucellosis vaccines is crucial for effective disease control. This study examined the immunogenicity and protective efficacy of the Lpp-OmpA-BtaE fusion protein, a construct combining the lipoprotein outer membrane protein A (Lpp-OmpA) with Brucella trimeric autotransporter E (BtaE), co-administered with Freund’s adjuvant (FA), in protecting against B.melitensis infection in a murine model.Vaccination with Lpp-OmpA-BtaE + FA conferred superior protection compared to the Lpp-OmpA + BtaE construct alone. Notably, Lpp-OmpA-BtaE + FA immunization elicited robust B-cell responses characterized by the generation of specific antibodies with a Th1-biased profile, as evidenced by elevated IgG2a/IgG1 ratios. Moreover, Lpp-OmpA-BtaE + FAinjection significantly increased interferon-γ (IFN-γ)/interleukin-4 (IL-4)levels and CD8+/CD4+ T-cell ratio, further supporting the induction of cell-mediated immune responses. Furthermore, it effectively reduced bacterial burdens in the spleens of infected mice. These findings suggest that the Lpp-OmpA platform fused with BtaE represents a promising candidate for the development of an efficacious Brucellosis vaccine, potentially leading to a reduction in morbidity and mortality associated with the disease.